Decentering - from Ptolemaic to Planetary (or Oneness) Paradigm - Shakespeare, Rodney (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
The Ptolemaic paradigm put the Earth at the centre of the universe giving rulers a Divine Right (to rule) and awarding humans high status as God’s Children who had planetary dominion.  However, in the sixteenth century, the Copernican Revolution decentered the Earth and so began undermining the Divine Right although it continued the high status and planetary dominion. Three centuries later, Darwinian Evolution, establishing that Homo sapiens is only one species among many, decentered humans from their high status.  Nevertheless, it did not check the dominion.  Indeed, Evolution did the opposite and gave humans a licence to pillage.  Moreover, the licence exacerbated the aggressive tendencies of Homo economicus as developed by John Stuart Mill.  Influenced by Malthus and Tennyson, Herbert Spenser then united Darwin and Mill proclaiming Survival of the Fittest thereby encouraging the imperialism and economic expansionism which would plunder the planet and result in today’s environmental crises. However, the Planetary (or Oneness) Paradigm, in a third decentering, remembers that humans are part of, and not separate from, the planet as a whole and enables Homo economicus to evolve into Homo co-operans thereby creating beneficial outcomes and enabling A Shared World View.